In-furrow fluopyram nematicide efficacy for Rotylenchulus reniformis management in cotton production. (February 2021) - Grabau, Zane J.; Liu, Chang; Schumacher, Lesley A.; Small, Ian M.; Wright, David L.
Abstract: In-furrow nematicide application is a primary method for managing Rotylenchulus reniformis (Linford and Oliveira, 1940) in cotton ( Gossypium hirsutum L.). Fluopyram is a relatively new non-fumigant nematicide and field data is needed to determine its efficacy at managing R. reniformis (reniform nematode, RN) in cotton production. To investigate, two experiments, consisting of multiple small plot field trials per experiment, were conducted in Quincy, FL. The first experiment evaluated optimal fluopyram application rate by comparing 0, 105, 131, 158, 184, and 236 g a.i./ha. The second experiment compared aldicarb, a common non-fumigant nematicide in cotton, with two fluopyram formulations, one at 184 g a.i./ha and another at 199 g a.i./ha. In the first experiment, fluopyram reduced RN abundances in 2 of 3 trials, and 236 g fluopyram/ha provided the most consistent management of RN soil populations, while 158 and 184 g fluopyram/ha were effective in one trial each. At 131 g a.i./ha or above, any fluopyram rate tested improved cotton yield compared with untreated in one trial, but did not affect yield in any other trial. In the second experiment, aldicarb reduced RN egg abundances in roots compared with untreated or fluopyram treatments. None of the nematicides affected yield in the second experiment. In summary, fluopyram was inconsistent for managing RN on cotton. Highlights: Fluopyram nematicide efficacy at managing reniform nematode on cotton was tested. Fluopyram managed reniform nematode, but not consistently. The highest fluopyram (236 g a.i./ha) was most consistently effective.